Research on the normality of the plastic strain vector to the yield surface in RC sections - Girgin, Konuralp; Girgin, Z. Canan; Aksoylu, M. Gunhan (SPRINGER, 2014)
In this study, the normality condition of the plastic strain vector to the yield surface utilized for elastic-perfectly plastic materials is investigated for reinforced concrete (RC) sections. If the plastic strain vector can be assumed outward normal to the yield surface in RC sections under combined biaxial bending and axial load, the components of the vector can be expressed by a single parameter. Thus, the material nonlinearity can be simplified through the extended plastic hinge concept based on the normality condition. In this study the normality of the plastic strain vector is verified via numerical examples in symmetrically reinforced rectangular and circular RC sections subjected to biaxial bending and axial load for various configurations of longitudinal reinforcement.
Keywords: Reinforced concrete sections; Elastic-perfectly plastic material; Yield surface; Plastic strain vector; Flow rule; REINFORCED-CONCRETE SECTIONS; LOAD INCREMENT METHOD; AXIAL FORCE; CROSS-SECTIONS; COMPOSITE; COLUMNS; SUBJECT; DESIGN; MODEL; Construction & Building Technology; Engineering; Materials Science